Rancang Bangun Robot Quadropod Pendeteksi Halangan Dengan Menggunakan Logika Fuzzy - Atmaja, Brahmanto Utama; Harianto, Harianto; Ihyaudin, Ihyaudin (Journal JCONES, 2012)
Many robots have been made by experts mimic the shape of the anatomy of living creatures. One of the many popular robots are legged robots. Utilization of legged robots in industry is able to pass through the places that are not possible using a wheeled robot, for example excess legged robot is up and down the stairs. To support the development and use of more advanced control systems, the authors proposed the creation Robot Quadropod Obstacle Detector Using Fuzzy Logic. Fuzzy logic is used to regulate the movement of four-foot robot with the help of two servo motors in each leg as well as data input in the form of obstacle distance detected by the ultrasound sensor. With the movement of the foot 2 DOF (Degree Of Freedom) system, the robot can run well and be able to control the speed of the robot foot steps in accordance with the detected obstacle distance from the use of fuzzy logic while using only one ultrasound sensor.